(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Virtual discussions have become a common practice in the corporate sector. This article aims to outline the most effective strategies that can be used to establish trust in virtual discussions. To achieve this goal, several techniques were employed, including direct observation, interviews with negotiators, analysis of 2,000 virtual conversations, and monitoring a company’s virtual negotiations for around 24 months. Based on a thorough analysis of the content, the main findings highlighted effective strategies that can build trust in remote negotiations. These include selecting the appropriate form of virtual communication, providing multiple contact options, ensuring reliable and high-quality connections, maintaining constant accessibility, and creating an organized and conducive environment for communication, free from interruptions. This article offers a fresh perspective on virtual business negotiations that is useful to academics, negotiators, and other professionals. It presents practical strategies for establishing trust in virtual negotiations.